Adult Attachment Style, Spirituality, and Religiosity among Individuals in Treatment for Substance Use Disorders - Diaz, Naelys (2012)
Spirituality and religiosity are considered to be protective factors in the treatment of substance abuse. Little is known, however, about how adult attachment style may be associated with levels of spirituality and religiosity. This study explored adult at- tachment styles among individuals in inpatient treatment for substance abuse and dependence and determined if there were significant differences between spirituality and/or religiosity variables by adult attachment style within the sample. Results indicated that neither of the religiosity variables varied by attachment style, but that one of two subscales in the spirituality measure, existential purpose and meaning, did vary significantly. Specifically, differences between the Secure attachment group and the Fearful group were highly statistically significant, with the Secure group reporting higher levels ofexistential purpose and meaning. Differences between the Secure group and the Dismissing group approached significance, again with the Secure group’s scores being higher. This study has shown that social work and other mental health professionals serving individuals with substance related problems must understand that, in their efforts to increase spirituality in their clients as a protection against relapse, they should recognize the impact that attachment style may have on their clients’ spiritual lives